The Effect Of Transportation On Regional Economic Development In Aceh Tamiang Regency - Iqbal, Muhammad; Rahim Matondang, Abdul; Rujiman, Rujiman (International Journal of Science, Technology & Management, 2023)
This research seeks to identify and explain the impact of transportation on regional economic development in the Aceh Tamiang Regency. This quantitative study relies on secondary data from the Central Statistics Agency (BPS) of Aceh Tamiang Regency for theyears 2013 to 2021. The method of data analysis is executed using the collected secondary data, which is first processed to determine the value of each variable. After collecting the data, it is tabulated so it can be analyzed using correlation and regression statistics to test the proposed hypotheses. According to the findings of this study, the calculated F of the output is 12.357 > 5.79, indicating that the length of the road and the number of vehicles have no significant effect on the growth of regional income in Aceh Tamiang Regency. In other words, the length of the road and the number of vehicles have no significant effect on employment opportunities in the Aceh Tamiang Regency, as determined by the F test